2014
DOI: 10.1038/nutd.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

High saturated-fat and low-fibre intake: a comparative analysis of nutrient intake in individuals with and without type 2 diabetes

Abstract: Objective:The aim of dietary modification, as a cornerstone of type 2 diabetes (T2DM) management, is to optimise metabolic control and overall health. This study describes food and nutrient intake in a sample of adults with T2DM, and compares this to recommendations, and to intake in age, sex, body mass index (BMI) and social-class matched adults without T2DM.Design:A cross-sectional analysis of food and nutrient intake in 124 T2DM individuals (64% male; age 57.4±5.6 years, BMI 32.5±5.8 kg m−2) and 124 adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 51 publications
5
21
0
Order By: Relevance
“…Less than 10% of patients with diabetes and of the general population fulfilled the recommendations for intake of SFA, reflecting a general problem of the abundance of SFA (and refined carbohydrates) in the western diet. Our findings are in accordance with findings in several observational studies, where intakes of total fat and saturated fat exceed recommendations, while the opposite goes for the intake of fibre in patients with diabetes (6,7,10,11).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Less than 10% of patients with diabetes and of the general population fulfilled the recommendations for intake of SFA, reflecting a general problem of the abundance of SFA (and refined carbohydrates) in the western diet. Our findings are in accordance with findings in several observational studies, where intakes of total fat and saturated fat exceed recommendations, while the opposite goes for the intake of fibre in patients with diabetes (6,7,10,11).…”
Section: Discussionsupporting
confidence: 92%
“…The latest national survey of dietary habits in Denmark (2011 -13) concluded that the Danish diet was too high in fat and carbohydrates (added sugar) and too low in dietary fibre compared to the dietary guidelines (5). Only a few studies have investigated dietary intake and adherence to the recommendations in patients with diabetes (6)(7)(8)(9)(10)(11), in general reporting poor adherence for most macronutrients. Dietary studies comparing patients with diabetes with the general population have not previously been reported.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Compared to studies elsewhere, this study has reported the highest energy contribution from carbohydrate (73.0%) among any type 2 diabetic population [10,24,25]. This can be explained by the fact that the usual Ugandan diet comprises of starches as the staple foods on the plate, accompanied by small amounts or infrequent sauce/relish which is usually a plant protein, animal protein or a vegetable [26].…”
Section: Discussionmentioning
confidence: 89%
“…Castetbon et al showed that diabetes patients had higher intakes of proteins and lower intakes of sugars and total carbohydrates while they consumed fewer calories and globally exhibited a healthier diet [32]. Many studies have shown that individuals with diabetes consumed more proteins [33,34,35], meats [32,33,34,35,36], sodium [37,38] and also more fat, saturated, monounsaturated and polyunsaturated fat and cholesterol and lower sugars, than individuals without diabetes [21,22,35,36,37,38,39], which is consistent with our findings. In contrast, in our study, the higher consumption of fat was mainly from polyunsaturated fat.…”
Section: Discussionmentioning
confidence: 99%